LEARNING SKILLS AS PART CONTENT MASTERY SERVICE IN GUIDANCE COUNSELING - Umami, Ida (Universitas Muhammadiyah Metro, 2015)
Abstrack: This paper aimed to get the profile of efforts of guidance teachers in improving students’ learning skills. It is hoped that this papaer is useful for guidance teachers, subject teachers and student as well in improving their learning skills. The learning skill quality of the students was low while their learning problems were on medium level. Guidance given by guidance teachers to students to master learning skills was not yet optimal. There was cooperation among teachers and guidance teachers but it was still limited to physics teachers and it had skills came from both guidance teachers and students themselves.Keywords: guidance teachers, learning skill, students.